Arduino robot bonanza - McComb, Gordon (New York : McGraw-Hill Education, 2013)
'Create high-tech walking, talking, and thinking robots. Breathe life into the robots of your dreams--without advanced electronics or programming skills. Arduino robot bonanza shows you how to build autonomous robots using ordinary tools and common parts. Learn how to wire things up, program your robot's brain, and add your own unique flair'--P. [4] of cover.
Includes index.
Keywords: Robots -- Control systems; Arduino (Programmable controller)